Pathogenesis and Targeted Therapy of Epilepsy - N'Gouemo, Prosper (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Epilepsy is one of the most prevalent neurological disorders and is characterized by recurrent seizures resulting from abnormal neuronal excitability in the central nervous system. Despite the availability of thirty-six antiseizure medications, about one-third of patients with epilepsy do not respond to the pharmacological treatment and develop a so-called "pharmaco-resistant epilepsy" or "refractory epilepsy." Thus, there is an urgent need to develop novel, effective therapies based on novel mechanisms underlying neuronal excitability that leads to seizures. This reprint's original research papers and review articles highlight unknown mechanisms underlying pharmaco-resistant resistant epilepsy, epileptogenesis, and seizure suppression.